Evaluation of conventional and digital radiography capacities for distinguishing dental materials on radiograms depending on the present radiopacifying agent - Antonijević, Djordje; Ilić, Dragan; Medić, Vesna; Dodić, Slobodan; Obradović-Djuričić, Kosovka; Rakočević, Zoran (Vojnosanitetski pregled, 2014)
Bacgroun/Aim. The radiopacity of an endodontic material can considerably vary as measured on film and a digital sensor. Digital radiography offers numerous advantages over convential film-based radiography in dental clinical practice regarding both diagnostic capabilities and postintervention procedures. The aim of this study was to investigate the capacity of conventional and charge-conpled device (CCD) based digital radiography to detect material on radiograph depending on the radio-pacifying agent present in the material. Methods. Experimental cements were formulated by mixing Portland cement with the following radiopacifying agents: zinc oxide (ZnO), zirconium oxide (ZrO2), titanium dioxide (TiO2), barium sulphate (BaSO4), iodoform (CHI3), bismuth oxide (Bi2O3) and ytterbium trifluoride (YbF3). In addition, 5 endodontic materials comprising Endomethasone®, Diaket®, N2®, Roth 801® and Acroseal® were investigated to serve as control. Per three specimens of each material were radiographed alongside an aluminum step wedge on film (Eastman Kodak Company®, Rochester, NY) and a CCD-based digital sensor (Trophy Radiologie®, Cedex, France). Radiopacity values were calculated by converting the radiographic densities of the specimens expressed as a mean optical densities or mean grey scale values into equivalent thickness of aluminum. Results. Two-way ANOVA detected no significant differences with respect to the imaging system (p > 0.05), but the differences were significant with respect to radiopacifier (p < 0.001) and the interaction of the two factors (p < 0.05). Paired t-test revealed significant differences between the methods used for pure Portland cement, all concentrations of BaSO4 and CHI3, 10% and 20% additions of ZrO2 and Bi2O3 and 10% and 30% addition of YbF3 (p < 0.05). Conclusion. The materials which incorporate CHI3 or BaSO4 as radiopacifying agents are expected to be significantly more radiopaque on a digital sensor than on film. During clinical practice one should concern to the quality of contrast assessement obtained by digital according to conventional radiography.
Keywords: radiography; dental; digital; contrast media; dental cements